Schiller’s Response to Voltaire in 'Die Jungfrau von Orleans': Enlightened or Romantic? - Ritchie Robertson (Modern Languages Open)
Schiller’s play Die Jungfrau von Orleans (The Maid of Orléans, 1801) is a response to Voltaire’s Pucelle, but not a straightforward antithesis. Schiller agreed with Voltaire’s religious scepticism. Nor is it adequate to contrast Voltaire’s poem with Schiller’s play as the antithesis of Enlightenment versus Romanticism. What Schiller objected to in Voltaire, as is made clear in the treatise Über naive und sentimentalische Dichtung (On Naïve and Sentimental Poetry, 1795), was that his wit too often failed to address the emotions. Schiller’s own testimony that his play was intended to speak to the heart is confirmed by the enthusiastic emotional response it received from contemporary audiences. Since 1945, however, German commentators have been uncomfortable with the patriotic call to arms issued by Schiller’s heroine and with her energetic slaughter of enemy soldiers (in contrast to the historical Jeanne, who did not fight). Some commentators have played down the historical and political content, maintaining that Johanna enacts a tragic drama of commitment, fall from grace and redemption, and becomes a sublime heroine. Some excuse her slaughter as necessary obedience to God’s will. This essay argues that Johanna’s patriotic mission is relatively unproblematic and her religious calling highly problematic. Johanna’s eagerness to repel the English invaders understandably appealed to German audiences who had recently witnessed the brutal French occupation of Germany’s western provinces. Her religious mission, however, seems suspect when she ascribes it both to the voice of God and to spirits speaking to her from the ‘Druid tree’ near her home, and when she shows a desire for personal glory. Citing the slaughters recounted in the Old Testament (and sharply criticised by Voltaire), Johanna embodies the religious fanaticism (Schwärmerei) that the Enlightenment deplored. Behaving like a killing machine, she loses her personal autonomy. Her use of Catholic imagery also makes her suspect, in view of Schiller’s consistent opposition to Catholicism. Her subsequent experiences embody a psychological development, rendered plausible by Schiller’s medical knowledge, which cures her fanaticism, restores her personal autonomy and replaces her egoism with humility. When she is captured by the English, she appeals directly to God and is rewarded by a miracle that enables her to join in the fighting and save the life of the king of France. Mortally wounded, she dies amid her admiring compatriots (another departure from history). Schiller did not simply dismiss religious belief. Following Hume rather than Voltaire, he understood it as emotional projection, in which valuable feelings were directed towards an imaginary object. In Johanna’s development, her emotions are redirected towards the liberation of her country and purified of their egoistic taint. Although often loosely described as ‘Romantic’, the play belongs to an area of literary history intermediate between the Enlightenment and Romanticism, and often lamely called préromantisme or Spätaufklärung, which demands further investigation.